A European Public Sphere United by Football: A Comparative Quantitative Text Analysis of German, Norwegian, Polish and Spanish Football Media - Jonas Biel; Tobias Finger; Arne Niemann; Vincent Reinke; Radosław Kossakowski; Jens Jungblut; Dobrosław Mańkowski; Ramón Llopis-Goig (JCMS: Journal of Common Market Studies, 2023)
The ability of the European community to respond to the multiple crises threatening the European Union and Europe depends in part on citizens' shared European identity giving legitimacy and support to communal action. Men's elite European club football is an example of a cultural practice that is highly Europeanised, reaches diverse audiences and is a known carrier of collective identities. This article examines the emergence of a European public football sphere through the convergence of football coverage across national media spaces, serving as a foundation for European identity constructions. It connects the concept of a European public sphere to the Europeanisation and mediatisation of football and its potential effects on European identity formation. Results indicate a convergence of football coverage around high-profile and high-status aspects of European football, creating a strongly aligned, homogenous but exclusive European public football sphere that leaves many parts of Europe on the sidelines.
Keywords: 330; European identity; European public sphere; Europeanisation; football